Antarctic Skuas as bioindicators of local and global mercury contamination - COSTA, Erli Schneider; SANTOS, Maria Mercedes; CORIA, Nestor Rubem; TORRES, João Paulo Machado; MALM , Olaf; ALVES, Maria Alice dos Santos (Revista Teste SPGG, 2019)
Mercury (Hg) is a non-essential metal, sometimes extremely toxic, and its presence in the food-web may threaten the wildlife. In seabirds, even low levels of Hg can reduce egg production and the chances of embryos and chicks survival; high levels of this element lead to erratic behavior, loss of appetite and weight, and cellular damages in organs as kidneys can be detected. According to some authors, among 50 to 93% of the total Hg accumulated by the birds through diet can be excreted throughout the feathers during the molting process. In this way, feathers can be used as an excellent non-invasive biomonitor. The objective of this paper was to compared mercury (Hg) levels in feathers of adults and chicks of Catharacta maccormicki(Cma) and C. lonnbergi (Clo) sampled in the Antarctic Peninsula, to identify biomonitors of Hg to the region using non-invasive samples methods. We found Hg significantly higher levels in adults of Cma comparing with Clo adults (U'=841.00, p<0.01) and also with chicks of both species (q>3.398, p<0.01). We did not find significant differences comparing Clo adults and chicks of both species (U'=16.00, p<0.05), and comparing Cma breeding in different areas (q>3.398, p<0.05) or Clo (U'= 62.00, p < 0.05). The Hg levels variation may be justified mainly by differences in migration patterns. The adults of the species that migrate to more polluted areas (Cma) presented the highest levels of Hg and can be considered a promising indicator of global contamination. In another way, Clo and chicks of both species are good indicators of local Hg contamination, suffering the direct influence of contamination in the Antarctic environment.